Analisis Pengaruh Pola Konsumsi Makanan Pemberian Asi Dan Kesehatan Lingkungan Terhadap Status Gizi Balita Di Wilayah Kerja Puskesmas Mekarsari Lebak Propinsi Banten - Iva Nurazijah; Rahayu Khairiah (Jurnal Keperawatan Muhammadiyah, 2022)
Background :. The problem of undernutrition and malnutrition is still a major problem in Indonesia. Malnutrition if allowed to continue to develop has an impact on brain development. Initial observations of researchers still found toddlers who were under the red line, had difficulty eating conditions, were breastfed and an environment that relatively did not meet health requirements. Researchers are interested in further analyzing the nutritional status of children under five, feeding patterns and environmental health in the working area of PKM Mekarsari.Purpose of Writing: To determine the pattern of feeding, breastfeeding and environmental health on the nutritional status of children under five in the working area of the Mekarsari Public Health Center, Tangerang Regency in 2021.Research Methods: The design of this research is correlational descriptive with a cross sectional approach. The population is all children aged 12-60 months who are in the working area of the Mekarsari Public Health Center as many as 335 toddlers, for this study a sample of 182 toddlers was taken, using simple random sampling technique. Data were analyzed using univariate, bivariate and multivariate analysis with regression and correlation tests.Â  Research Results: The results of the univariate analysis showed that most of the toddlers (45%) had a good diet, but breastfeeding (45%) was relatively lacking, the environmental health level of 45% was relatively good, the results of multivariate bivariate analysis showed eating patterns and then breastfeeding. and environmental health show that there is an influence on the nutritional status of children under five in the Mekarsari working areaConclusions and Suggestions: the results of the study show that there are still toddlers with poor nutritional status, it is hoped that the Mekarsari Health Center can provide more services to families who have children under five and can prioritize promotive and preventive primary services through IEC activities or health counseling in order to improve health status. community, especially in improving the nutritional status of children under five by reducing and suppressing the incidence of malnutrition or malnutrition